Purine Ionotropic (P2X) Receptors - L. Koles; S. Furst; P. Illes (Current Pharmaceutical Design, 2007)
Purinergic signaling is involved in the proper functioning of virtually all organs of the body. Although in some cases purines have a major influence on physiological functions (e.g. thrombocyte aggregation), more often they are just background modulators contributing to fine tuning of biological events. However, under pathological conditions, when a huge amount of adenosine 5'-triphosphate (ATP) can reach the extracellular space, their significance is increasing. ATP and its various degradation products activate membrane receptors divided into two main classes: the metabotropic P2Y and the ionotropic P2X family. This latter group, the purine ionotropic receptor, is the object of this review. After providing a description about the distribution and functional properties of P2X receptors in the body, their pharmacology will be summarized. In the second part of this review, the role of purines in those organ systems and body functions will be highlighted, where the (patho)physiological role of P2X receptors has been suggested or is even well established. Besides the regulation of organ systems, for instance in the cardiovascular, respiratory, genitourinary or gastrointestinal system, some special issues will also be discussed, such as the role of P2X receptors in pain, tumors, central nervous system (CNS) injury and embryonic development. Several examples will indicate that purine ionotropic receptors might serve as attractive targets for pharmacological interventions in various diseases, and that selective ligands for these receptors will probably constitute important future therapeutic tools in humans.
Keywords: pathophysiology